New insights into the effects on blood pressure of diets low in salt and high in fruits and vegetables and low-fat dairy products - Sacks Frank M; Vollmer William M; Svetkey Laura P (Current Controlled Trials in Cardiovascular Medicine, 2001)
Abstract Results from the recent Dietary Approaches to Stop Hypertension (DASH)-Sodium trial provide the latest evidence concerning the effects of dietary patterns and sodium intake on blood pressure. Participants ate either the DASH diet (high in fruits, vegetables and low-fat dairy products, and reduced in saturated and total fat) or a typical US diet. Within each diet arm, participants ate higher, intermediate, and lower sodium levels, each for 30 days. The results indicated lower blood pressure with lower sodium intake for both diet groups. Although some critics would argue otherwise, these findings provide important new evidence for the value of the DASH diet and sodium reduction in controlling blood pressure.